Assessing the potential of submaximal extended duration exercise as an adjunct treatment for sub-acute schizophrenic in-patients: a pilot study - Munnik, James Barry (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
Research into the therapeutic potential of aerobic exercise has proven fruitful over the past few years; however, no true experimental research undertakings have investigated the psychological benefits of aerobic exercise with schizophrenic semi-acute in-patients. The main objective of this thesis was to seek out evidence for the possibility that aerobic (submaximal long duration) exercise could be considered an adjunct treatment for hospitalised schizophrenic in-patients. In order to accomplish this objective the effects of a 45-minute walking programme, completed three days a week, for five weeks, was investigated. Various areas of mental health were explored in search of evidence of the therapeutic potential of aerobic exercise. These areas included, amongst other things: transfer and discharge rates, improvements in mood levels - Beck Depression Inventory-II (BDI-II; Beck, Steer, and Brown, 1996) Xhosa version; decreasing of anxiety levels (Beck Anxiety Inventory (BAI; Beck and Steer, 1993), Xhosa version); improved Global Assessment of Functioning (GAF; DSM-IV), Scale Scores; and decreases in the number of symptoms patients exhibited. 22 schizophrenic inpatients were randomly selected for this study and randomly assigned to either an aerobic (long duration submaximal) treatment group or (primarily anaerobic) control group. Results revealed that statistical significance could not be found in any of the treatment group's t-test results; despite the treatment group generally bordering on significance more so than the control group. Out of the five variables studied (Positive Symptoms, Negative Symptoms, BAI, BDI-II, and GAF Scale) three variables (Negative Symptoms, BDI-II, and GAF Scale) in the treatment group bordered more on significance than did the control group. Thus three (60 %) out of the five areas studied revealed that the treatment group had more significant results. This suggests an overall impression that the treatment group responded slightly better. The Researcher recommended that aerobic exercise therapy be considered a treatment protocol in psychiatric institutions and offered further suggestions pertaining to the effective implementation of these programmes. Included in these recommendations were motivational strategies and warnings about the possible negative effects of exercise therapy. A supplemental goal of this thesis was to explore all of the previously offered theoretical psychological mechanisms of positive mental change; and to seek out evidence, for or against these forces. Participants were given pre- and post- treatment quantitative interviews; as well as, qualitative posttreatment interviews where their phenomenological responses were analysed to seek out evidence of these mechanisms. Evidence of various causative factors was found and a new theoretical mechanism was proposed in this thesis.
Keywords: Aerobic exercises -- Therapeutic use; Schizophrenia; Schizophrenia -- Treatment; Exercise therapy